Mast cell‐nerve interactions correlate with bloating and abdominal pain severity in patients with non‐celiac gluten / wheat sensitivity. Issue 6 (5th February 2020) - Giancola, Fiorella; Volta, Umberto; Repossi, Roberta; Latorre, Rocco; Beeckmans, Dorien; Carbone, Florencia; Van den Houte, Karen; Bianco, Francesca; Bonora, Elena; Gori, Alessandra; Costanzini, Anna; Boschetti, Elisa; et al.
Abstract: Background: Gastrointestinal (GI) and extra‐GI symptoms/manifestations represent key clinical features of patients with non‐celiac gluten/wheat sensitivity (NCG/WS). This study aimed to investigate neuro‐immune (focusing on mast cells, MCs) interactions in the duodenal submucosa of patients with NCG/WS. Methods: Submucosal whole mounts from duodenal biopsies of 34 patients with self‐reported NCG/WS, 28 with celiac disease (CD), 13 with functional dyspepsia (FD), and 24 healthy controls (HC) were analyzed by immunohistochemistry. Quantitative data on neuronal and MCs density and the percentage of MCs in close vicinity to nerves were obtained, and correlations among neurons, MC density and MC‐nerve distance (D), and symptoms were assessed in the three groups. Key Results: The number of submucosal neurons was not different among groups. In NCG/WS, MC density was not different from HC, while it was slightly increased vs. CD ( P = .07) and significantly decreased vs. FD ( P < .05). The percentage of MCs close to nerves ( D < 15 µm) was similarly increased in all three pathological groups vs. HC ( P < .001). In NCG/WS, MC infiltration correlated with bloating ( P = .001) and abdominal pain severity ( P = .03) and the percentage of MCs in proximity to neurons correlated with the number of GI symptoms (D < 5 µm; P = .05), bloating and abdominal pain severity ( D < 15um; P = .01). Conclusions and Inferences: Submucosal MC infiltration and the close (within 15 µm) MC‐to‐nerve proximity in the duodenum of NCG/WS patients are features providing a histopathological basis to better understand GI symptoms in this condition. Abstract : Duodenal mast cells infiltration and their interaction with submucosal nerves.